2019
DOI: 10.1111/hdi.12811
|View full text |Cite
|
Sign up to set email alerts
|

Repeated mechanical thrombectomy for acute ischemic stroke in a dialysis patient: A case report and literature review

Abstract: Mechanical thrombectomy (MT) can significantly improve the prognosis of patients with large vessel occlusion (LVO) stroke. It is still unclear whether repeated MT in a short period of time is safe and effective in patients with renal failure and atrial fibrillation (AF). We present the case of an LVO patient with AF and uremia who was successfully treated with MT for M1 segment occlusion of the right middle cerebral artery (MCA) and achieved a good outcome. Fifteen days after the first MT, the patient's stroke… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 34 publications
0
1
0
Order By: Relevance
“…A number of studies have confirmed that endovascular therapy can significantly improve the prognosis of patients with large vessel occlusion stroke. [ 7 12 ] However, some patients outside the treatment window lose the chance of thrombolysis or endovascular therapy and even in patients receiving IVT or endovascular treatment, there are still a considerable number of patients with neurological deficits that have not been significantly improved, or even cannot benefit from treatment. Therefore, there is still much room for optimization in the treatment of AIS patients, and it is necessary to find effective drugs to improve the prognosis of AIS patients.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have confirmed that endovascular therapy can significantly improve the prognosis of patients with large vessel occlusion stroke. [ 7 12 ] However, some patients outside the treatment window lose the chance of thrombolysis or endovascular therapy and even in patients receiving IVT or endovascular treatment, there are still a considerable number of patients with neurological deficits that have not been significantly improved, or even cannot benefit from treatment. Therefore, there is still much room for optimization in the treatment of AIS patients, and it is necessary to find effective drugs to improve the prognosis of AIS patients.…”
Section: Introductionmentioning
confidence: 99%